Design and Development of Novel Floating Drug Delivery Systems - Urmila C Patel; AmitKumar R. Dhankani; Sunil P. Pawar (International Journal of Membranes, 2024)
Recent advances in science and technology have greatly aided in the creation of novel drug delivery methods, especially in addressing physiological issues including irregular stomach emptying times and brief stomach residence periods. Long-term stomach absorption is the goal of gastro-retentive dosage forms (GRDF). Floating drug delivery systems, expanding or swelling systems, polymer-based bioadhesive systems, high-density systems, and other ways that postpone stomach emptying are just a few of the techniques that have been developed to do this. With an emphasis on the main floating mechanism utilized to accomplish stomach retention, this review attempts to gather contemporary literature. There are many advantages to sustained oral release of gastrointestinal dose forms, particularly for medications that act locally in the stomach and are absorbed in the upper regions of the gastrointestinal system. The review includes the physiology of the stomach, variables that affect the excipient's ability to retain food after it has been consumed, and methods for creating both multi-unit and single-unit hydrodynamically balanced systems. It goes into great length about these systems' classification, formulation, and evaluation in addition to discussing a few applications.
Keywords: Floating drug delivery systems; Gastric residence time; classification; evaluation in-vitro and in vivo; multiple units; single unit